A randomised controlled trial of the efficacy of the ABCD Parenting Young Adolescents Program: rationale and methodology - Burke Kylie; Brennan Leah; Roney Sarah (BMC, 2010)
Abstract Background The transition to adolescence is a time of increased vulnerability for risk taking and poor health, social and academic outcomes. Parents have an important role in protecting their children from these potential harms. While the effectiveness of parenting programs in reducing problem behavior has been demonstrated, it is not known if parenting programs that target families prior to the onset of significant behavioral difficulties in early adolescence (9-14 years) improve the wellbeing of adolescents and their parents. This paper describes the rationale and methodology of a randomised controlled trial testing the efficacy of a parenting program for the promotion of factors known to be associated with positive adolescent outcomes, such as positive parenting practices, parent-adolescent relationships and adolescent behavior. Methods/Design One hundred and eighty parents were randomly allocated to an intervention or wait list control group. Parents in the intervention group participated in the ABCD Parenting Young Adolescents Program, a 6-session behavioral family intervention program which also incorporates acceptance-based strategies. Participants in the Wait List control group did not receive the intervention during a six month waiting period. The study was designed to comply with recommendations of the CONSORT statement. The primary outcome measures were reduction in parent-adolescent conflict and improvements in parent-adolescent relationships. Secondary outcomes included improvements in parent psychosocial wellbeing, parenting self-efficacy and perceived effectiveness, parent-adolescent communication and adolescent behavior. Conclusions Despite the effectiveness of parenting programs in reducing child behavioral difficulties, very few parenting programs for preventing problems in adolescents have been described in the peer reviewed literature. This study will provide data which can be used to examine the efficacy of a universal parenting interventions for the promotion of protective factors associated with adolescent wellbeing and will add to the literature regarding the relationships between parent, parenting and adolescent factors. Trial Registration Australian New Zealand Clinical Trials Registry ACTRN12609000194268.